Bioactive polymersomes self-assembled from amphiphilic.PPO-glycopolypeptides: synthesis, characterization, and dual-dye encapsulation - Das, Soumen; Sharma, Dharmendar Kumar; Chakrabarty, Suman; Chowdhury, Arindam; Sen Gupta, Sayam (Langmuir, 2015)
Glycopolypeptide-based polymersomes have promising applications as vehicles for targeted drug delivery because they are capable of encapsulating different pharmaceuticals of diverse polarity as well as interacting with specific cell surfaces due to their hollow structural morphology and bioactive surfaces. We have synthesized glycopolypeptide-b-poly(propylene oxide) by ROP of glyco-N-carboxyanhydride (NCA) using the hydrophobic amine-terminated poly(propylene oxide) (PPO) as the initiator. This block copolymer is composed of an FDA-approved PPO hydrophobic block in conjugation with hydrophilic glycopolypeptides which are expected to be biocompatible. We demonstrate the formation of glycopolypeptide-based polymersomes from the self-assembly of glycopolypeptide-b-poly(propylene oxide) in which the presence of an ordered helical glycopolypeptide segment is required for their self-assembly into spherical nanoscale (similar to 50 nm) polymersomes. The polymersomes were characterized in detail using a variety of techniques such as TEM, AFM, cryo-SEM, and light-scattering measurements. As a model for drugs, both hydrophobic (RBOE) and hydrophilic (calcein) dyes have been incorporated within the polymersomes from solution. To substantiate the simultaneous entrapment of the two dyes, spectrally resolved fluorescence microscopy was performed on the glycopeptide polymersomes cast on a glass substrate. We show that it is possible to visualize individual nanoscale polymersomes and effectively probe the dyes colocalization and energy-transfer behaviors therein as well as investigate the variation in dual-dye encapsulation over a large number of single polymersomes. Finally, we show that the galactose moieties present on the surface can specifically recognize lectin RCA(120), which reveals that the polymersomes surface is indeed biologically active.

Fluorescent probes for the detection of cyanide ions in aqueous medium: cellular uptake and assay for beta-glucosidase and hydroxynitrile lyase - Agarwalla, Hridesh; Gangopadhyay, Monalisa; Sharma, Dharmendar Kumar; Basu, Santanu Kumar; Jadhav, Sameer; Chowdhury, Arindam; Das, Amitava (Journal of Materials Chemistry B, 2015)
A chemodosimteric reagent (1) for the efficient detection of cyanide species (CN- and/or HCN) in aq. medium as well as under physiological conditions has been described. Selective reaction of the cyanide species with this reagent in the presence of all common interfering anions, amino acids and glutathione (GSH) led to the generation of the corresponding cyanohydrin derivative. The formation of the cyanohydrin derivative of the probe is associated with a visually detectable change in solution fluorescence in aq. buffer medium with 1.9 mu M NaCN, the threshold limit set by WHO for the safe drinking water and this makes this fluorogenic sensor an ideal candidate for in-field applications. An apparent switch on the luminescence response, ultralow detection limit, low response time, cell membrane permeability and insignificant toxicity are key features of a probe molecule, which gives it a distinct edge over previously reported chemodosimetric reagents for the detection of cyanide species (CN- or HCN) in an aqueous environment. This methodology could be used for developing a generalized and efficient fluorescence-based assay for crucial enzymes like beta-glucosidase and hydroxynitrile lyase. Furthermore, spectrally-resolved fluorescence microscopy measurements on single-cells revealed that this sensor molecule could also be used for imaging the cellular uptake of cyanide species from aq. solution contaminated with NaCN. Our results confirmed that statistical analysis of integrated intensity and transition energy obtained from the emission spectra collected over various microscopic sub-cellular regions can potentially be used to discriminate the effects of local cellular environments and that due to cyanide detection.

Glycopolypeptide-grafted bioactive polyionic complex vesicles (PICsomes) and their specific polyvalent interactions - Pandey, Bhawana; Mahato, Jaladhar; Cotta, Karishma Berta; Das, Soumen; Sharma, Dharmendar Kumar; Sen Gupta, Sayam; Chowdhury, Arindam (ACS Omega, 2016)
Glycopolypeptide-based self-assembled nano-/microstructures with surface-tethered carbohydrates are excellent mimics of glycoproteins on the cell surface. To expand the broad repertoire of glycopolypeptide-based supramolecular soft structures such as polymersomes formed via self-assembly of amphiphilic polymers, we have developed a new class of polyionic complex vesicles (PICsomes) with glycopolypeptides grafted on the external surface. Oppositely charged hydrophilic block copolymers of glycopolypeptide(20)-b-poly-L-lysine(100) and PEG(2k)-b-poly-L-glutamate(100) [PEG = poly(ethylene glycol)] were synthesized using a combination of ring-opening polymerization of N-carboxyanhydrides and ``click'' chemistry. Under physiological conditions, the catiomer and aniomer self-assemble to form glycopolypeptide-conjugated PICsomes (GP-PICsomes) of micrometer dimensions. Electron and atomic force microscopy suggests a hollow morphology of the PICsomes, with inner aqueous pool (core) and peripheral PIC (shell) regions. Owing to their relatively large (similar to micrometers) size, the hollowness of the supramolecular structure could be established via fluorescence microscopy of single GP-PICsomes, both in solution and under dry conditions, using spatially distributed fluorescent probes. Furthermore, the dynamics of single PICsomes in solution could be imaged in real time, which also allowed us to test for multivalent interactions between PICsomes mediated by a carbohydrate (mannose)-binding protein (lectin, Con-A). The immediate association of several GP-PICsomes in the presence of Con-A and their eventual aggregation to form large insoluble aggregate clusters reveal that upon self-assembly carbohydrate moieties protrude on the outer surface which retains their biochemical activity. Challenge experiments with excess mannose reveal fast deaggregation of GP-PICsomes as opposed to that in the presence of excess galactose, which further establishes the specificity of lectin-mediated polyvalent interactions of the GP-PICsomes.